Mecanismo de autenticação descentralizada de usuários em redes definidas por software - CORDEIRO, Ramon da Gama (2019)
The decentralized authentication mechanism allows users to acess resources of a Software-Defined Network (SDN) with security, available and reliability. The SDN paradigm has grow in recent years through researchers’ work, but still there is challenges of ensure security acess and availability of network. Many papers make use of centralized authentication with only one controller to manager the mesh. This paper proposes a mechanism of security acess in networks of multiples controllers, through of decentralization of user authentication process among managers of control plane in order to hinder improper acess and guarantee that the services are always available.